Characteristics of the edible film made from Kappaphycus alvarezii of Sumenep seawaters, Madura - Hafiludin Hafiludin; Desti Yulia Radika Prameswari; Mojiono Mojiono (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2025)
Edible film is a primary packaging in the form of a thin layer that covers food products, and it is usually made from hydrocolloids, lipids, and mixtures of both. Edible film from seaweed carrageenan (Kappaphycus alvarezii) extracts may serve as an alternative to plastic packaging, which is environmentally friendly and safe for consumption. This research aims to analyze the proximate composition ofKappaphycus alvareziisamples (lab-scale drying and conventional drying) and investigate its effects on physical characteristics (thickness values, solubility in water, water vapor transmission rate, elongation,and tensile strength) of the edible film. The research was carried out in several stages: sampling, sample preparation, carrageenan extraction, and edible filmmaking. The research was carried out using a completely randomized design with five treatments, namely the addition of 1%, 2%, 3%, 4%, and 5% (w/v) carrageenan extract. The research results showed significant differences in proximate values(water, ash, fat, fiber, and carbohydrates) between seaweed dried by farmers and seaweed dried in the laboratory. The addition of carrageenan extract significantly affected the edible film's thickness, water solubility, and tensile strength. The best characteristics were obtained at a concentration of 2% carrageenan extract, resulting in a thickness of 0.12 mm, solubility in water of 60.43%, water vapor transmission rate of 5.77 g/cm2/hour, elongation of 251.33%, and tensile strength of2.42 Mpa.The results of this research are essential for the development of packaging technology in the future.